Indole alkaloids from the Marquesan plant Rauvolfia nukuhivensis and their effects on ion channels. (January 2015) - Martin, Nicolas J.; Ferreiro, Sara F.; Barbault, Florent; Nicolas, Mael; Lecellier, Gaël; Paetz, Christian; Gaysinski, Marc; Alonso, Eva; Thomas, Olivier P.; Botana, Luis M.; Raharivelomanana, Phila
Graphical abstract: Highlights: The Polynesian plant Rauvolfia nukuhivensis produces a large diversity of indole alkaloids. Six original alkaloids were isolated belonging to the biosynthetically related alkaloids ajmaline, sarpagine, macroline. Some of them exhibit an interesting biological activity on hERG ion channels. Docking studies were undertaken to illustrate results on the biological activity. Abstract: In addition to the already reported nukuhivensiums1 and2, 11 indole alkaloids were isolated from the bark of the plant Rauvolfia nukuhivensis, growing in the Marquesas archipelago. The known sandwicine (3 ), isosandwicine (4 ), spegatrine (8 ), lochneram (9 ), flavopereirine (13 ) have been found in this plant together with the norsandwicine (5 ), isonorsandwicine (6 ), N b -methylisosandwicine (7 ), 10-methoxypanarine (10 ), nortueiaoine (11 ), tueiaoine (12 ). The structure elucidation was performed on the basis of a deep exploration of the NMR and HRESIMS data as well as comparison with literature data for similar compounds. Norsandwicine, 10-methoxypanarine, tueiaoine, and more importantly nukuhivensiums, were shown to significantly induce a reduction of IKr amplitude (HERG current). Molecular modelling through docking was performed in order to illustrate this result.